2022
DOI: 10.3390/ijms23084403
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Bioconversion of trans-Resveratrol to δ-Viniferin Using Conditioned Medium of Grapevine Callus Suspension Cultures

Abstract: δ-Viniferin is a resveratrol dimer that possesses potent antioxidant properties and has attracted attention as an ingredient for cosmetic and nutraceutical products. Enzymatic bioconversion and plant callus and cell suspension cultures can be used to produce stilbenes such as resveratrol and viniferin. Here, δ-viniferin was produced by bioconversion from trans-resveratrol using conditioned medium (CM) of grapevine (Vitis labruscana) callus suspension cultures. The CM converted trans-resveratrol to δ-viniferin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…For example, in the case of resveratrol, the pioneering work of Langkage and Pryce ( Langcake and Pryce, 1977 ) showed that the main compound obtained was trans -δ-viniferin, derived from a C-8/C-3′ dimerisation using horseradish peroxidase. These results have since been observed in numerous studies on laccases and peroxidases ( Wilkens et al, 2010 ; Gindro et al, 2017 ; Righi et al, 2020 ; Huber et al, 2022a ; Park et al, 2022 ). This point could be explained by the fact that the presence of an exocyclic conjugated double bond increases the delocalization of the radical and thus its stability.…”
Section: Resultssupporting
confidence: 63%
“…For example, in the case of resveratrol, the pioneering work of Langkage and Pryce ( Langcake and Pryce, 1977 ) showed that the main compound obtained was trans -δ-viniferin, derived from a C-8/C-3′ dimerisation using horseradish peroxidase. These results have since been observed in numerous studies on laccases and peroxidases ( Wilkens et al, 2010 ; Gindro et al, 2017 ; Righi et al, 2020 ; Huber et al, 2022a ; Park et al, 2022 ). This point could be explained by the fact that the presence of an exocyclic conjugated double bond increases the delocalization of the radical and thus its stability.…”
Section: Resultssupporting
confidence: 63%
“…The α,β diastereoselectivity could also be found in natural phytophenol oligomers. This is because that phytophenol oligomerization is essentially a process of phytophenol interacting with free radical, under the condition of oxidase catalysis . Thus, it quite resembles antioxidant product formation.…”
Section: Results and Disscussionmentioning
confidence: 99%
“…This is because that phytophenol oligomerization is essentially a process of phytophenol interacting with free radical, under the condition of oxidase catalysis. 30 Thus, it quite resembles antioxidant product formation. However, as seen in SI 17, there was no pair of epimers among 40 phytophenol oligomers, despite each of them has two chiral atoms and should possess 4 possible stereoisomers.…”
Section: Synthesis Of 36-dimethoxylcatechol (12)mentioning
confidence: 96%